Characterization of technology from four (4) panel paintings of hieromonk Dionysius from Fourna, author of “Hermeneia of the Painting Art” and comparison with his manuscrip - Μαφρέδας, Θωμάς (Πανεπιστήμιο Πελοποννήσου, 2018)
The contribution of hieromonk Dionysius of Fourna and his treatise: ―Hermeneia of Painting Art‖ is decisive because it gathers all the previously scattered advices and information about the construction of portable icons –panel paintings-, which are mentioned in his text, in an autonomous chapter. In addition, his essay becomes a reference point for many years, both for the writing of various "Hermeneias" of painting in the wider Greek and Balkan space, as well as for the exploration of the construction technology and the study of the iconographic types of post-Byzantine orthodox painting. In the construction technology section, the information quoted by hieromonk Dionysius is probably the only recorded source about the construction stages for post-Byzantine panel paintings and for the materials used during this process. Characteristic are the information about the construction concerning the gesso layer preparation, the gilding technique and process, the pigments that he uses, the varnish recipes, and so on. In this context, four panel paintings signed by Dionysius, which are kept in the sacristy of the Transfiguration Church in his native village, in Fourna, were selected for scientific research. A research protocol of imaging techniques and physicochemical analysis was carried out, aiming to characterize the materials and the construction technology applied by Dionysius concerning the construction of the four panel paintings and compare the results with all the relative references mentioned in his work "Hermeneia of Art Painting" in order to ascertain moreover, by using scientific methods, if all that he mentions in his work, he also applies them in practice. Initially, the research protocol was set up and then the relevant research procedures were carried out, which were digital microscopy (DM), X-ray fluorescence (XRF), optical microscopic observation (OM), microchemical tests, scanning electron microscopy with energy dispersive X-ray analysis (SEM/EDX) and Infrared Spectroscopy (FTIR). The microscopic observations and the physicochemical analyses were carried out in the Laboratory of Physical and Chemical Research of the National Gallery in Athens, in the Laboratory of Archaeometry of the University of Peloponnese in Kalamata, in the Laboratory of Physical and Chemical Techniques of the Technological Educational Institute of Athens, Department of Conservation of Antiquities and works of Art and at NCSR Demokritos, Department of Materials Science. The obtained results will help to study Dionysius painting technique and at the same time will perform an attempt to compare his technique with his earlier treatise ―Hermeneia of Painting Art‖. It was the first time that an extensive physicochemical research on Dionysius selected panel paintings concerning his painting technique was applied.
Keywords: Διονύσιος , ο εκ Φουρνά , π. 1670-π. 1745 -- Ερμηνεία της ζωγραφικής τέχνης; Ζωγραφική -- Τεχνική; Ζωγραφική -- Ανάλυση; Χρωστικές ουσίες -- Ανάλυση; Αγιογραφία -- Θέματα, μοτίβα; Αρχαιολογική χημεία -- Μεθοδολογία; Ανάλυση χρωμάτων και υλικών; Αρχαιολογική χημεία; Διονύσιος ο εκ Φουρνά; Αγιογραφία